2013
DOI: 10.1111/1574-6968.12284
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid-mediated fitness advantage ofAcinetobacter baylyiin sulfadiazine-polluted soil

Abstract: LowGC-type plasmids conferring resistance to sulfonamides have been frequently isolated from manure and manured soil. However, knowledge on the dynamics of plasmid-carrying populations in soil and their response to the presence of sulfonamides is scarce. Here, we investigated effects of the sulfonamide resistance conferring plasmid pHHV216 on the fitness of Acinetobacter baylyi BD413 in soil after application of manure with or without the sulfonamide antibiotic sulfadiazine (SDZ). The persistence of A. baylyi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 26 publications
(35 reference statements)
0
10
0
Order By: Relevance
“…Recombinant whole-cell bacterial bioreporters that respond to specific classes of antibiotics or report on specific stress responses in bacteria have also been constructed (Melamed et al, 2012;van der Meer and Belkin, 2010). Dual strain single-species assays employing both antibiotic-resistant and sensitive strains may further be developed to measure minimal selective concentrations for antibiotic resistance development (Gullberg et al, 2011) in various environmental matrices (Ashbolt et al, 2013;Jechalke et al, 2013).…”
Section: Assessing Effects On Single Speciesmentioning
confidence: 99%
“…Recombinant whole-cell bacterial bioreporters that respond to specific classes of antibiotics or report on specific stress responses in bacteria have also been constructed (Melamed et al, 2012;van der Meer and Belkin, 2010). Dual strain single-species assays employing both antibiotic-resistant and sensitive strains may further be developed to measure minimal selective concentrations for antibiotic resistance development (Gullberg et al, 2011) in various environmental matrices (Ashbolt et al, 2013;Jechalke et al, 2013).…”
Section: Assessing Effects On Single Speciesmentioning
confidence: 99%
“…In two independent competition experiments with plasmid-free and plasmid-carrying Acinetobacter baylyi BD413 performed in soil microcosms, Jechalke et al [72] demonstrated that the LowGC-type plasmid pHHV216 conferred a fitness advantage to Acinetobacter baylyi BD413 in soils that had received manure spiked with sulfonamide antibiotic sulfadiazine. Plasmid carriage had a disadvantage when the selective pressure by SDZ was absent.…”
Section: Plasmid Host Range Determination and Plasmid Cost And Benmentioning
confidence: 99%
“…In addition to the many competition studies performed in liquid cultures, recent work has shown the effect of antibiotic presence on the competitiveness of plasmid-bearing strains in soil. In two independent competition experiments with plasmid-free and plasmid-carrying Acinetobacter baylyi BD413 performed in soil microcosms, Jechalke et al [72] demonstrated that the LowGC-type plasmid pHHV216 conferred a fitness advantage to Acinetobacter baylyi BD413 in soils that had received manure spiked with sulfonamide antibiotic sulfadiazine. Plasmid carriage had a disadvantage when the selective pressure by SDZ was absent.…”
Section: Plasmid Host Range Determination and Plasmid Cost And Benefitsmentioning
confidence: 99%